Socially constructed or physiologically informed? Placing humans at the core of understanding cooling needs - Mazzone, A; Khosla, R (Elsevier, 2021)
Space cooling is expected to become an indispensable energy service for health and wellbeing for most of the world's population by 2050. While climatic events, technologies, socio-economic indicators, and features of the built environment are the most researched drivers for space cooling, we offer an alternative, multidimensional review that places humans and their physiological interactions with space, culture and society at the centre of this investigation. We aim to expand the understanding of thermal comfort beyond the dominant technical focus and examine the broader, though largely underutilized, literature on material culture, everyday practices and sociocultural influences on how a range of human factors influence people's preferences for cooling thermal comfort. We integrate these perspectives with insights from psychology and neuro-architecture to discuss the influence of space in the perceptions of thermal comfort beyond heat-exchange. We navigate the different studies reviewed from a variety of fields within the social science and humanities and argue that cooling needs and preferences are grounded in both cultural and corporeal perceptions, and are the result of individual subjective experience of external stimuli within the body, culture, space, and society. We argue that placing humans at the core of understanding the origins of cooling needs is key to enabling a more sustainable cooling future, and identify key areas of future research.